The Relationship between Domestic and Outward Foreign Direct Investment: The Role of Industry-Specific Effects - Pontus Braunerhjelm; Lars Oxelheim; Per Thulin (The Research Institute of Industrial Economics (IUI), 2004)
Previous research has been inconclusive as regards the effect of outward foreign direct investment (FDI) on domestic investments. In this article we show that this inconclusiveness can be explained at a disaggregated level as a function of the way industries are organized. Based on a simple model including monitoring and trade costs, we argue that a complementary relationship can be expected to prevail in vertically integrated industries, whereas a substitutionary relationship can be expected in horizontally organized production. The empirical analysis confirms a significant difference between the two categories of industry as regards the impact of outward FDI on domestic investment. The results may thus have profound policy implications.
Keywords: F12; F21; F23; G34; 330; FDI; Gross Domestic Investment; Industry-Specific Effects; Monitoring Costs; Trade Costs; Direktinvestition; Investition